2020
DOI: 10.1038/s41598-020-63492-9
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for detection unveils the intricacy of wild boar and rabbit co-occurrence patterns in a Mediterranean landscape

Abstract: the patterns of species co-occurrence have long served as a primary approach to explore concepts of interspecific interaction. However, the interpretation of such patterns is difficult as they can result from several complex ecological processes, in a scale-dependent manner. Here, we aim to investigate the co-occurrence pattern between european rabbit and wild boar in an estate in central portugal, using two-species occupancy modelling. With this framework, we tested species interaction for occupancy and detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Our findings also further highlight the importance of considering biological scale in habitat use investigations [89,90], as the true extent of the impact of lion occurrence on wild dog would not have been evident from analyses restricted to a single spatial scale. Finally, our study emphasizes the importance of also accounting for interspecific effects on detection when investigating co-occurrence, as recently highlighted by others [91].…”
Section: Methodological Considerations and Main Study Limitationssupporting
confidence: 72%
“…Our findings also further highlight the importance of considering biological scale in habitat use investigations [89,90], as the true extent of the impact of lion occurrence on wild dog would not have been evident from analyses restricted to a single spatial scale. Finally, our study emphasizes the importance of also accounting for interspecific effects on detection when investigating co-occurrence, as recently highlighted by others [91].…”
Section: Methodological Considerations and Main Study Limitationssupporting
confidence: 72%
“…Therefore, further studies should focus on the relationship between the coexistence patterns and population density/relative abundance of the two species. Additionally, though occupancy models are increasingly applied to data from wildlife camera‐trap surveys to estimate distribution, habitat use, and patterns of species co‐occurrence of unmarked animals (Burton et al, 2015 ; Estevo et al, 2017 ), the interpretation of co‐occurrence patterns is inherently difficult (Barros et al, 2020 ). Several studies have demonstrated that detection frequency and estimates of detection probability and occupancy were sensitive to movement speed (or the magnitude of animal movement) (Neilson et al, 2018 ; Stewart et al, 2018 ), especially for animal occupied large‐ and medium‐sized home ranges with low population density (Neilson et al, 2018 ), whereas occupancy estimates for scenarios with small home ranges closely matched the simulated asymptotic PAO (proportion of area occupied) (Neilson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variables associated to vegetation composition and structure were assessed, in situ, within the minimum convex polygon that encompassed all the sett entrances, plus a buffer of 2 m. The Simpson diversity index [ 38 ] was estimated based on the herbaceous, shrub and bare soil cover in each polygon. Later, we built a Geographic Information System (GIS; QGIS ® version 2.8.3—Wien, Beaverton, OR, USA [ 39 ]), that encompassed remote sensing information regarding the: type of soil (data provided by the Companhia das Lezíria, S.A, Samora Correia, Portugal); land use [ 38 ]; location of setts, game feeding stations and watering pivots, paved and unpaved roads and water points (to allow the estimation of the distance of each sett from these landmarks; data provided by the Companhia das Lezíria, S.A.); grazing pressure per plot (data provided by the Companhia das Lezíria, S.A.); and wild boar occurrence determined in a previous study [ 40 ].…”
Section: Methodsmentioning
confidence: 99%